The Effect Of Game Application “Mr. Detective” In Students’ Vocabulary Mastery - Elvira Glaudia Lubis, Zulfitri (Ability: Journal of Education and Social Analysis, 2022)
The objective of this research is to determine the effect of game application “Mr. Detective” in vocabulary mastery on verbs for students at tenth grade of SMA Swasta Cerdas Murni. This research is experimental quantitative and was conducted on June 2021. In this research, the sample was from students of class X MIPA 1 and X MIPA 2 with each class containing 36 students and a total sample were 72 students. Data were collected through multiple choice tests on verbs and then through quantitative procedures to both classes that are the experimental class for X MIPA 1 and the control class for X MIPA 2 were given a test twice such as a pre-test and a post-test using different media. In the experimental class using game application media and for the control class using conventional media. Based on the results of the research, it is known that the use of media in the experimental class has a higher score than the control class with a mean value of 80.00 for the experimental class and 70.56 for the control class. This proves that there is a significant effect through this game.